THE IMPACT OF THE PROFESSIONAL DEGRADATION PROCESS AMONG PROFESSOR-TEACHERS WORKING AT THE UNIVERSITY ON THE EFFICIENCY OF STUDENTS' ACADEMIC ACTIVITY - Kurbanova Zilola Alisher kizi (Bright Mind Publishing, 2025)
This article focuses on the mechanisms of pedagogues’ activity and interest in their profession fading away, and at the same time, it is pointed out how to help people in this situation. Empirical study of the socio-psychological features of the process of professional burnout and practical recommendations on the prevention of professional burnout have been developed. Factors affecting the formation of the process of professional fading in teachers, the deepening of communication with the client, self-evaluation, relations in the institution where he works, neuroticism (anxiety), attitude towards the object of work, social factors such as extroversion – psychological factors are determined on the basis of empirical research, and information is given about cases of professional burnout among teachers. According to the manifestation of professional burnout by age, length of service, resistance (contradiction), “tension level”, “feeling of fatigue”, “inadequacy of emotional reaction”, “reduced feeling of fulfilling professional obligations” ( reduction), features of “anxiety and depression”; conclusions based on gender psychological characteristics, such as men’s ability to absorb reality, inability to pass stressors as quickly as women, man’s sense of duty and responsibility as family breadwinner and provider.
Keywords: Professional burnout, emotional burnout, professional stress, professional identity, professional self, professional competence, professional cooperation, professional competence.